Diagnostic utility of the lymphoid screening tube supplemented with CD34 for Ogata score calculation in patients with peripheral cytopenia. Issue 1 (1st January 2019) - Muyldermans, Astrid; Florin, Lisa; Devos, Helena; Cauwelier, Barbara; Emmerechts, Jan
ABSTRACT: Objectives: The diagnosis of myelodysplastic syndrome (MDS) is not always straightforward in the absence of objective markers such as ringed sideroblasts, an excess of blasts or clonal cytogenetic abnormalities. Moreover, the lack of specificity of morphological dysplasia makes the differentiation between MDS and other causes of peripheral cytopenia difficult. The WHO 2016 classification of MDS recognizes multiparameter flow cytometry (MFC) as an adjuvant tool for MDS diagnosis. An easily applicable MFC protocol based on CD34 and CD45 is proposed by Ogata et al . Furthermore, in the diagnostic workup of patients with peripheral cytopenia, the integration of MFC by means of a Lymphoid Screening Tube (LST) is recommended by the EuroFlow™ consortium. The aim of this study was to investigate whether the LST, supplemented with CD34, can be used to calculate the Ogata score, thereby obviating the need to run different flow cytometric tubes. Methods: Bone marrow samples from 108 patients with peripheral cytopenia were analyzed (MDS n  = 32; non-MDS n  = 76). The LST used in the present study was based on the tube designed by the EuroFlow™ consortium, but with addition of CD34 and without TCRγδ. Results: Rather low sensitivities of 55% in low-grade MDS patients and 80% in high-grade MDS patients were observed. However, a high specificity of 92% was found in the non-MDS group. Conclusion: Besides screening for clonal lymphocytes, plasma cells and blasts, an LST supplemented with CD34 allows the calculation of the Ogata score as an adjuvant tool in the diagnostic workup of cytopenic patients suspected of MDS.